Pneumopericardium after rigid bronchoscopy for foreign body removal - (:unkn) unknown (My University, 1998)
We report a case of post-bronchoscopy pneumopericardium in a 2 1/4 -year-old child with 20 days history of foreign body aspiration which developed after high frequency and high pressure ventilation during bronchoscopy to maintain adequate arterial oxygen saturation. Pneumothorax and subcutaneous emphysema was not observed. It showed a self-limited course and resolved within three days. Convalescence was uneventful. The risk of pneumopercardium should always be considered when high pressure ventilation is applied during bronchoscopy.
Keywords: Foreign body; Pediatric anesthesia; Pneumopericardium; Rigid bronchoscopy